2006
DOI: 10.2214/ajr.05.0383
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution CT of the Chest in Children and Young Adults Who Were Born Prematurely: Findings in a Population-Based Study

Abstract: High-resolution CT in young people of preterm birth revealed abnormal radiologic findings in 81.3% of the patients at age 10 years and 92.5% at age 18 years. Linear, triangular, and subpleural opacities were the most common. The reproducibility of the applied scoring system was acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 86 publications
5
61
1
3
Order By: Relevance
“…They performed HRCT in inspiration and expiration and found a decrease in hypoattenuated areas from expiratory CT (26%) to inspiratory CT (14%), compatible with air trapping. In fact, the emphysema score in these subjects was 0% (44). Therefore, it seems likely that hypoattenuation seen in HRCT images of preterm survivors is not caused by deranged alveolar development but rather by air trapping.…”
Section: Discussionmentioning
confidence: 83%
“…They performed HRCT in inspiration and expiration and found a decrease in hypoattenuated areas from expiratory CT (26%) to inspiratory CT (14%), compatible with air trapping. In fact, the emphysema score in these subjects was 0% (44). Therefore, it seems likely that hypoattenuation seen in HRCT images of preterm survivors is not caused by deranged alveolar development but rather by air trapping.…”
Section: Discussionmentioning
confidence: 83%
“…The presence of emphysema could not be predicted by perinatal or postnatal factors or a personal history of smoking. The differences in the findings with the study by Aukland et al (Aukland et al, 2006) may be attributed to the fact that the study by Wong et al (Wong et al, 2008) represents a group of adults who were highly selected, constituting 19 subjects (14%) with severe perinatal disease from the original cohort of 133 subjects. These subjects all had moderate/severe BPD compared to the other studies that had included ex-preterm subjects with no or mild BPD.…”
Section: Structural Lung Diseasementioning
confidence: 62%
“…The same authors also demonstrated a reduction in FEV 1 in subjects with a high HRCT chest score (Wong et al, 2008). Subjects with hypoattenuation had a lower FEV 1 than those without hypoattenuation (mean FEV 1 80.9% vs. 89.8%, respectively) (Aukland et al, 2006). Increased number of days with oxygen treatment also predicted an increase in the total HRCT score (Wong et al, 2008).…”
Section: Structural Lung Diseasementioning
confidence: 82%
See 1 more Smart Citation
“…Studies have demonstrated that high-resolution computed tomography (HRCT) is more sensitive than radiographs for evaluating lung disease, 9,10 but little has been described in the literature on HRCT in relation to the neonatal period or shortly afterwards, or in relation to the consistency of its interpretation. [11][12][13][14][15][16][17] Studies on the reliability of chest radiographs on patients with chronic lung disease have shown wide variation in the interpretation of images by radiologists. [18][19][20] Bloomfield et al showed poor interobserver agreement for pulmonary parenchymal abnormalities on chest x-rays of premature infants in neonatal intensive care units.…”
Section: Introductionmentioning
confidence: 99%